Collaborative and Culturally Grounded Learning in a University Directing Course: Actualizing Tradition and Student Identity Formation - Astuty Pulukadang, Mimy; Triyanty Pulukadang, Wiwy (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to examine how cultural traditions are actualized through collaborative and culturally grounded learning processes in a university-level directing course. It specifically addresses the tension between local cultural values and globalizing influences by exploring the role of arts education in cultural initiation, identity formation, and community engagement. Method: A qualitative research design was employed. Data were collected through in-depth interviews with lecturers, students, and local artists involved in the directing course. The data were analyzed thematically to identify patterns related to collaborative practices, the integration of local cultural values, learning outcomes, and sustainability challenges. Results: The findings reveal four main themes: (1) collaborative creative processes between students and local artists; (2) the integration of regional cultural values into directing practice; (3) the influence of culturally grounded learning on students’ artistic competence and identity formation; and (4) institutional and logistical challenges affecting program sustainability. Collaboration with local artists enabled students to access living cultural knowledge, deepening their understanding of symbolic meanings, ethical values, and moral philosophies embedded in local narratives. This process strengthened students’ cultural identity, social sensitivity, creative confidence, and reflective artistic practice. Novelty: This study offers a culturally responsive pedagogical model that positions collaboration with local cultural communities as a core strategy in directing education. It contributes a contextualized framework for integrating living traditions into higher arts education, highlighting its transformative potential beyond technical skill development.